Development and Characterization of a Wee1 Kinase Degrader. Issue 1 (16th January 2020) - Li, Zhengnian; Pinch, Benika J.; Olson, Calla M.; Donovan, Katherine A.; Nowak, Radosław P.; Mills, Caitlin E.; Scott, David A.; Doctor, Zainab M.; Eleuteri, Nicholas A.; Chung, Mirra; Sorger, Peter K.; Fischer, Eric S.; et al.
Summary: The G1/S cell cycle checkpoint is frequently dysregulated in cancer, leaving cancer cells reliant on a functional G2/M checkpoint to prevent excessive DNA damage. Wee1 regulates the G2/M checkpoint by phosphorylating CDK1 at Tyr15 to prevent mitotic entry. Previous drug development efforts targeting Wee1 resulted in the clinical-grade inhibitor, AZD1775. However, AZD1775 is burdened by dose-limiting adverse events, and has off-target PLK1 activity. In an attempt to overcome these limitations, we developed Wee1 degraders by conjugating AZD1775 to the cereblon (CRBN)-binding ligand, pomalidomide. The resulting lead compound, ZNL-02-096, degrades Wee1 while sparing PLK1, induces G2/M accumulation at 10-fold lower doses than AZD1775, and synergizes with Olaparib in ovarian cancer cells. We demonstrate that ZNL-02-096 has CRBN-dependent pharmacology that is distinct from AZD1775, which justifies further evaluation of selective Wee1 degraders. Graphical Abstract: Highlights: A selective Wee1 degrader was generated by conjugating pomalidomide to AZD1775 Wee1 degradation induced G2/M accumulation at lower doses than Wee1 inhibition Wee1 degradation synergized with Olaparib in ovarian cancer cells Abstract : Li, Pinch et al. develop and characterize the first selective Wee1 degrader, ZNL-02-096, by linking the clinical candidate inhibitor, AZD1775, to the cereblon-binding ligand, pomalidomide. They demonstrate that ZNL-02-096 exhibits cereblon-dependent pharmacology, induces G2/M phase accumulation and apoptosis at lower doses than AZD1775, and synergizes with Olaparib.